Type 2 diabetes and physical activity: barriers and enablers to diabetes control in Eastern India. (2019) - Pati, S.; Lobo, E.; Pati, S.; Desaraju, S.; Mahapatra, P.
Abstract: Introduction: Type 2 diabetes (T2D) has tremendous morbidity burden owing to disease management and complication prevention. Behavior modification identified as a key to management includes healthy diet and regular physical activity (PA). This study aims to identify patterns and preferences of PA of T2D patients and explore perceived enablers and barriers for diabetes control in Bhubaneswar. Methods: Cross-sectional, facility-based study conducted in the private sector from June to August 2014 recruited 321 T2D patients using semi-structured questionnaires. Descriptive statistics and associations of PA were computed. Results: Almost two-thirds of patients (59%) were reported performing PA frequently. Majority patients cited walking as the most preferred mode of PA (79%) with 41% performing PA daily. Actual versus perceived weight was a complete mismatch with most patients misjudging their weight. Reasons for enabling PA included 'controlling diabetes' and 'doctor's advice' as key factors, while 'lack of time' and 'unwillingness' were main barriers among inactive patients. Conclusion: Counseling on PA by physicians during routine visits, along with tailored or patient-specific interventions should be considered. Focus on social support for positive behavioral changes and motivation play a central role in diabetes control.